2000
DOI: 10.1080/110241500447407
|View full text |Cite
|
Sign up to set email alerts
|

Patency of Autologous and Prosthetic Arteriovenous Fistulas in Elderly Patients

Abstract: A proximal brachioaxillary prosthetic AV graft is a good alternative as initial primary access in elderly patients who are not suitable for an autologous proximal AV fistula. At this age long term patency and conservation of proximal access sites are of minimum importance because of their limited life expectancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 16 publications
1
38
1
5
Order By: Relevance
“…1,4,27 Although the presence of a thrill has previously been used as evidence of technical success, clinical criteria are known to predict eventual maturation poorly. 13 In one study, Won and colleagues found that 93% of fistulas which failed to mature to be used for dialysis had a thrill present postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,27 Although the presence of a thrill has previously been used as evidence of technical success, clinical criteria are known to predict eventual maturation poorly. 13 In one study, Won and colleagues found that 93% of fistulas which failed to mature to be used for dialysis had a thrill present postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [20,21,22] have cast doubt on the value of creating an AV access in the very elderly starting HD, taking into account their short life expectancy. In addition, the probability of creating a successful AV access in elderly patients is lower than in younger patients, owing to the rigidity and frailty of their vascular network [17,18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…The overall survival of elderly patients is considerably lower, and the number of comorbidities is very high compared to their younger counterparts. Furthermore, several studies have shown that the adequate performance and maturation of a patent AVF for HD is more difficult to achieve in elderly patients owing to the limitations and rigidity of their compromised vascular network [17,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…However, controversy arises concerning the possibility of this principle implementation in elderly patients who, in addition, are often diabetic. The view has even been presented that the construction of an autogenous AVF in the elderly is associated with such a high risk of complications and failure that the formation of a prosthetic fi stula in the arm is the preferred option, especially in the context of a limited life expectancy [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%